Influencing factors associated with oral health among older hospitalized patients with ischemic stroke: A cross-sectional survey - Chengfei Wu; Huanhuan Huang; Wenxin Xu; Jinghong Li; Mei Chen; Qinghua Zhao (Elsevier, 2023)
Objective: To investigate the oral health status of older patients with ischemic stroke and analyze the influencing factors, providing valuable insights for developing effective oral health management strategies tailored for this population. Methods: A cross-sectional survey was conducted from January to June 2022, selecting 350 older patients with ischemic stroke from two tertiary hospitals in Chongqing. The Barthel Index (BI), Eating Assessment Tool (EAT-10), and Oral Health Assessment Tool (OHAT) were used to assess patients' self-care ability, swallowing function, and oral health status, respectively. A self-designed questionnaire was used to collect demographic information, disease-related information, and oral health behaviors of the patients. Binary logistic regression analysis was performed to analyze related influencing factors. Results: A total of 346 older patients with ischemic stroke were included, with 199 males and 147 females. The median total score of OHAT was 5 (total score range 0-16). Dental decay (91.7%, 278/303) and poor oral hygiene (92.2%, 319/346) were the main oral health problems in this population. Binary logistic regression analysis showed that sex, hyperlipidemia, stroke severity, stroke events, oral health behaviors, and care dependency were influencing factors for the oral health of this population (P < 0.05). Conclusion: The study revealed that healthcare professionals should strengthen the oral health assessment of older patients with ischemic stroke and implement individualized health education and management measures based on the characteristics of high-risk groups to promote their oral health.